Urazy w boksie – medyczny punkt widzenia = Injuries in boxing - a medical point of view - Kochański, Bartosz; Kałużna, Anna; Kałużny, Krystian; Kluska, Kamil; Płoszaj, Ola; Zukow, Walery; Hagner, Wojciech (Journal of Education, Health and Sport, 2015)
Kochański Bartosz, Kałużna Anna, Kałużny Krystian, Kluska Kamil, Płoszaj Ola, Zukow Walery, Hagner Wojciech. Urazy w boksie – medyczny punkt widzenia = Injuries in boxing - a medical point of view. Journal of Education, Health and Sport. 2015;5(9):559-568. ISSN 2391-8306. DOI10.5281/zenodo.31475 http://dx.doi.org/10.5281/zenodo.31475 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A559-568 https://pbn.nauka.gov.pl/works/635217 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 05.09.2015. Urazy w boksie – medyczny punkt widzenia Injuries in boxing - a medical point of view Bartosz Kochański1, Anna Kałużna1, Krystian Kałużny1, Kamil Kluska1, Ola Płoszaj2, Walery Zukow3, Wojciech Hagner1 1Katedra i Klinika Rehabilitacji, Wydział Nauk o Zdrowiu, Uniwersytet Mikołaja Kopernika w Toruniu 2Bydgoska Szkoła Wyższa w Bydgoszczy 3Wydział Kultury Fizycznej, Zdrowia i Turystyki, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Boks jest dyscypliną sportową polegającą na bezpośredniej walce na pięści dwóch zawodników, według określonych zasad przy ograniczonym polu uderzeń. Istotą boksu jest pokonanie przeciwnika poprzez pozbawienie go możliwości dalszej rywalizacji. Specyfika boksu wiążę się z dużym ryzkiem występowania urazów i kontuzji. W pracy zaprezentowano wybrane aspekty medyczne związane z boksem. Opisano czynniki ryzyka i przyczyny urazów i kontuzji w boksie. Dokonano analizy występowania urazów i kontuzji u pięściarzy. Zwrócono szczególną uwagę na uszkodzenia w obrębie głowy. Abstract Boxing is a sport consisting in direct fistfight two players, according to certain rules with a limited field of strokes. The essence of boxing is to beat your opponent by depriving it of the possibility of further competition. The specificity of boxing correlated with a risk of injuries and injury. The paper presents selected medical aspects associated with boxing. The paper described the risk factors and causes of injury in boxing. The work was done analysis of the existence of injury to the boxers. Special attention is paid to damage the head. Słowa kluczowe: boks, urazy, kontuzje, medycyna sportowa. Keywords: boxing, injury, injuries, sports medicine.